Phenotypical changes in Escherichia coli K12 after prolonged exposure to simulated microgravity - Chavez, Alba; Topolski, Collin; Hicks, Janelle; Villafania, Mitchell; Baez, Natalie; Burke, Marissa; Castillo, Hugo (Frontiers in Space Technologies, 2024)
Over the past few decades there has been a steady increase in interest in the study of the role of space environment in the genetic and phenotypical changes of microorganisms. More specifically, there are concerns with astronaut health being compromised during missions to the Moon and beyond from changes in many conditions. These include changes in the physiology of bacteria leading to alterations directly related to human health such as virulence and antibiotic resistance or to the functioning of life support systems such as the increase in biofilm formation in the water supply or treatment components. The effects of space conditions on microorganisms have been studied for more than a decade; however, there is still a need to determine the impact of the physiological effect of microgravity not only of bacterial growth, but also on the different virulence-related phenotypes that might contribute to phenotypic plasticity and microbial adaptation. This study focuses on deciphering the phenotypical changes of the commensal bacterium Escherichia coli K12 after growth under simulated microgravity conditions using a 2D microgravity analog. Using a 2D clinostat, E. coli was grown up to 22 days and used to measure changes in phenotypes commonly related to virulence. The phenotypes measured included cell population growth, biofilm development and the response to acidic pH and oxidative stress. Results from our studies showed the tendency to enhanced biofilm formation and a decreased resistance to oxidative stress and to grow under acidic conditions.